Understanding Multiple Interpretations on the Hadith that Husbands Allow Wives to have Outdoor Activities: A Study of Islamic Law Perspectives - M. Jakfar, Tarmizi; Fitria, Arifah (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2021)
Understanding the interpretation of a hadith is multifaceted, in which the Muslim clerics have multiple perspectives on certain hadith, including hadith on husband’s permission to wife to engage in outdoor activities. This is a library research, in which we explore some literature on this issue. The analysis technique used is descriptive-analytical and comparative, while the approach used is historical-sociological. The focuses of this study are threefold: to understand the mazhab(traditional) scholars’ and contemporary scholars’ perspectives, and to review the Islamic law on the Muslim clerics’ understanding of this issue. This paper concludes that mazhab scholars tend to understand the hadith textually, strictly and non-contextual-that is, asking permission to engage in outdoor activities is an obligation of the wife, otherwise it is considered disobedient to the husband. Meanwhile, contemporary scholars understand the hadith contextually and more flexible. They perceive that asking for permission to do outdoor activities is not an obligation; it is rather a recommendation for wives to seek for their husbands’ permission. In fact, in the recent times, wives working outdoor would in fact support husbands in fulfilling household’s needs. This difference can be understood because historically-sociologically the condition of the society has shifted and transformed. In the past, for instance, when women left the house they would cause danger in the middle of the desert such as robbery or wild animals. Meanwhile, nowadays mass communication and mass transportation have enabled families: husbands and wives to connect with each other. Likewise, when women going outdoor to seek knowledge, attending mosques for congregations, and or going for work, contemporary scholars do not see it as prohibited. Women doing activities outdoor has existed even by the time of the prophet and the companions, showing that most wives work outdoor for family benefits.